Cutaneous Delayed-Type Hypersensitivity to Surfactants. Issue 6 (November 2015) - Fowler, Joseph F.; Shaughnessy, Cristin N.; Belsito, Donald V.; DeKoven, Joel G.; Deleo, Vincent A.; Fransway, Anthony F.; Maibach, Howard I.; Marks, James G.; Mathias, C.G. Toby; Pratt, Melanie; Sasseville, Denis; Taylor, James S.; et al.
Abstract : Background: Repeated and prolonged use of surfactants can cause irritant as well as allergic contact dermatitis. Objective: This study reports the frequency of positive patch test results to surfactants tested on the North American Contact Dermatitis Group screening series including cocamidopropyl betaine (CAPB), amidoamine (AA), dimethylaminopropylamine (DMAPA), oleamidopropyl dimethylamine (OPD), and cocamide diethanolamide (CDEA), and correlations of positive reactions between CAPB and the other surfactants. Methods: This was a retrospective analysis of 10 877 patients patch tested between 2009 and 2014 to the surfactants CAPB, AA, DMAPA, OPD, and CDEA. Frequencies of positive reactions to these surfactants were calculated, and trends of reactivity between the surfactants analyzed. Conclusions: The OPD had the highest rate of positive patch reactions (2.3%) followed by DMAPA (1.7%), and CAPB (1.4%). The AA and CDEA had the lowest rate of positive reactions (0.8%). There was a high degree of overlap in positive patch tests between the surfactants. The CDEA was the least likely to coreact with another surfactant.